Global decadal measurements of methanol, ethene, ethyne, and HCN from the Cross-track Infrared Sounder - K. C. Wells; D. B. Millet; J. F. Brewer; V. H. Payne; K. E. Cady-Pereira; R. Pernak; S. Kulawik; S. Kulawik; C. Vigouroux; N. Jones; E. Mahieu; M. Makarova; et al. (Atmospheric Measurement Techniques)
Volatile organic compounds (VOCs) play an important role in modulating the atmosphere's oxidizing capacity and affect tropospheric ozone, carbon monoxide, formaldehyde, and organic aerosol formation. Space-based observations can provide powerful global information to advance our knowledge of these processes and their changes over time. We present here the development of new retrievals for four key VOCs (methanol, ethene, ethyne, and HCN) based on thermal infrared radiance observations from the satellite-borne Cross-track Infrared Sounder (CrIS). We update the Retrieval of Organics from CrIS Radiances (ROCR) algorithm developed previously for isoprene to explicitly account for the spectral signal dependence on the VOC vertical profile shape, and we apply this updated retrieval (ROCRv2) to derive column abundances for the targeted species across the full Suomi NPP CrIS record (2012–2023). The CrIS data are well correlated with ground-based Network for the Detection of Atmospheric Composition Change (NDACC) retrievals for methanol (r = 0.77–0.84); HCN and ethyne exhibit lower correlations (r = 0.36–0.44 and 0.56–0.65, respectively) with an apparent 40 % CrIS–NDACC disparity for ethyne. The results reveal robust global distributions of the target VOCs from known biogenic, biomass burning, and industrial source regions, and they demonstrate the impact of anomalous events such as the 2015–2016 El Niño. They also highlight the importance of accurate vertical profile constraints when evaluating and interpreting thermal infrared data records. Initial comparisons of the CrIS observations to predicted VOC distributions from the GEOS-Chem chemical transport model point to large uncertainties in our current understanding of the atmospheric ethene budget as well as to underestimated HCN, ethyne, and methanol sources.